2013
DOI: 10.5370/jeet.2013.8.3.603
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Inkjet-Printed Silver Patterns for Application to Printed Circuit Board (PCB)

Abstract: -In this paper, we describe the analysis of inkjet-printed silver (Ag) patterns on epoxycoated substrates according to several reliability evaluation test method guidelines for conventional printed circuit boards (PCB). To prepare patterns for the reliability analysis, various regular test patterns were created by Ag inkjet printing on flame retardant 4 (FR4) and polyimide (PI) substrates coated with epoxy for each test method. We coated the substrates with an epoxy primer layer to control the surface energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…In this work, it was also reported that narrow printed tracks may be more prone to faults under bending force. We used the 10 mm bending radius in bending tests, and our results are similar to those obtained with 16 mm bending radius presented in the work by Shin et al (2013). We did not observe a significant decrease in conductivity of the tested lines, and microscopic observation after tests did not reveal any damage in the samples tested.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In this work, it was also reported that narrow printed tracks may be more prone to faults under bending force. We used the 10 mm bending radius in bending tests, and our results are similar to those obtained with 16 mm bending radius presented in the work by Shin et al (2013). We did not observe a significant decrease in conductivity of the tested lines, and microscopic observation after tests did not reveal any damage in the samples tested.…”
Section: Resultssupporting
confidence: 85%
“…In the work by Shin et al (2013), the bending test of silver patterns on Polyethylene naphthalate (PEN) substrate was examined too. The effect of the bending radius and the line width was determined.…”
Section: Resultsmentioning
confidence: 99%
“…ECAs are extensively used in the assembly and packaging of electronic devices such as high-density multilayer interconnect substrates and high-speed, high-frequency circuits [ 1 , 6 , 7 , 8 , 9 , 10 ]. Among all of the ECAs, silver epoxy adhesives are most commonly used because of their high conductivity and stable contact resistance [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The direct printing of conductive ink has emerged as an important alternative to traditional lithography, which is a complex multistep method for producing conductive thin films or patterns that generates a lot of waste [ 1 ]. Many examples of the use of metallic inks in printed electronics have been reported, such as printed circuit boards [ 2 , 3 , 4 ], light-emitting diodes (LEDs) [ 5 , 6 ], flexible displays [ 7 , 8 ], radio frequency identification (RFID) tags [ 9 , 10 ], solar cells [ 11 , 12 ], and transparent electrodes [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%